REKONSTRUKSI LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH - Yusfitta Amanda; Moch. Shulthoni; Ahmad Ahsin Kusuma Mawardi (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2025)
CV Bambang Irawan Group is a business that has been operating for seven years in the internet services sector. Despite efforts to implement good accounting practices, this company's financial reports are still not in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). The main problems faced include a lack of systematization in recording transactions, minimal understanding of accounting standards, and limited skilled human resources. As a result, the resulting financial reports are inaccurate and difficult to understand, negatively impacting management decision making and stakeholder trust. This research aims to analyze and reconstruct the financial statements of CV Bambang Irawan Group so that they comply with SAK EMKM. With appropriate adjustments, it is hoped that financial reports can provide more reliable information, increase transparency, and make it easier to calculate tax liabilities. In addition, it is hoped that this research will become a reference for other MSMEs that face similar challenges in managing financial reports, as well as contribute to the development of better accounting practices among MSMEs, support local economic growth, and increase competitiveness in the market.